Research and development of compliant micro-electro-mechanical systems (MEMS) - Xiao, Zhongmin (2008)
This project investigates the fabrication and characterization of two-dimensional resoant micromirror device actuated by sol-gel deposited PZT thin films. The piezoelectric PZT thin films with silicon micromachining technology provide the advantages of high scanning frequencies and low driving voltages.